1996
DOI: 10.1021/jp953239o
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Bridged Adducts Formed by Chemical Reactions of Solid Aluminum Halides. Experimental Dilemma and ab Initio Calculations of Heterodimer Complexes AlX3−Y (X = F, Cl; Y = OH-, H2O)

Abstract: Starting from new experimental facts given by ESR, MS, and other physical and chemical methods, the role of bridged intermediates in the formation of catalytic active solids by thermal chemical reactions including the gaseous phase is discussed. Structures of oxygen-bridged adducts of AlF 3 and AlCl 3 with OH -and H 2 O have been explored at the HF and MP2 levels using 6-31G*, 6-31+G*, and 6-311G** basis sets. The reaction enthalpies of complex formation are calculated for several temperatures. Both hydroxyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…This fact was already observed in previous investigations of heterodimer complexes like AlX 3 ‚‚‚H 2 O. 3 At the HF level the BSSE is less than 20 kJ/mol for this basis set, whereas the other two basis sets result in BSSEs of about 30 kJ/mol (AlF 3 ‚‚‚2H 2 O) and 26 kJ/mol (AlCl 3 ‚‚‚2H 2 O). At the MP2 level these errors increase and we obtain values of up to 70 kJ/mol for the 6-31G* and 6-311G** basis sets, which mean almost 30% of the binding energy.…”
Section: Alx 3 ‚‚‚2h 2 O (X)fcl) Complexessupporting
confidence: 84%
See 2 more Smart Citations
“…This fact was already observed in previous investigations of heterodimer complexes like AlX 3 ‚‚‚H 2 O. 3 At the HF level the BSSE is less than 20 kJ/mol for this basis set, whereas the other two basis sets result in BSSEs of about 30 kJ/mol (AlF 3 ‚‚‚2H 2 O) and 26 kJ/mol (AlCl 3 ‚‚‚2H 2 O). At the MP2 level these errors increase and we obtain values of up to 70 kJ/mol for the 6-31G* and 6-311G** basis sets, which mean almost 30% of the binding energy.…”
Section: Alx 3 ‚‚‚2h 2 O (X)fcl) Complexessupporting
confidence: 84%
“…Previous calculations of heterodimer complexes predicted binding energies of about -122 to -130 kJ/mol for the AlF 3 ‚‚‚H 2 O complex and about -105 to -113 kJ/mol for the AlCl 3 ‚‚‚H 2 O complex. 3 Considering the zero-point vibrational energy correction, these values are predicted to be reduced by about 10 kJ/mol. However, as expected, these estimated values are still significantly larger than the binding energies per water molecule of the corresponding AlX 3 ‚‚‚2H 2 O complexes.…”
Section: Alx 3 ‚‚‚2h 2 O (X)fcl) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the number of isomeric structures that correspond to each AlF 3 •n(H 2 O) (n = 1−6) complex increases with n, we decided to limit our discussion to those whose relative energies do not exceed 20 kcal/mol with respect to the corresponding most stable structure. 14,17 We have not found any other geometrically stable isomer of AlF 3 •H 2 O in the 0−20 kcal/mol energy range (with respect to the global minimum 1); however, we verified that the isomeric structure 2 of AlF 3 •H 2 O (see Figure 1) that consists of HF fragment connected to the AlF 2 OH system via the F → Al dative bond (i.e., HF → AlF 2 OH) also corresponds to the local minimum. Even though the relative energy of 2 was estimated to be 31.6 kcal/mol, which indicates that such an isomer is not expected to be competitive with 1, we provide its structure for completeness (regarding our findings described in the subsequent sections).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies of the hydration processes of AlF 3 are rather sparse and seem incomplete (i.e., limited to the most stable AlF 3 hydrates). Moreover, the quantum chemical calculations (using Hartree–Fock, Møller–Plesset (MP) or density functional methods) have been performed only for the AlF 3 complexes with one, two, or three water molecules. Namely, (i) Ball determined (at the MP2/6-31G­(d,p) level) the gas phase equilibrium structure of the AlF 3 H 2 O in which the presence of two H-bonds was revealed; (ii) Scholz et al found three isomers of AlF 3 ·3H 2 O (by performing the B3LYP/6-31+G­(d) calculations) whose structures indicated the formation of either one or two H 2 O → AlF 3 dative bonds; (iii) Krossner et al evaluated binding energies for selected geometries (that were believed to be the global minima) of the AlF 3 ·2H 2 O and AlF 3 ·3H 2 O complexes . Even though it seems obvious that the presence of at least 5–6 water molecules should be taken into account while theoretically studying the hydration processes of AlF 3 , such calculations have not been undertaken thus far.…”
Section: Introductionmentioning
confidence: 99%